2007
DOI: 10.1016/j.jcrs.2006.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Quality of vision with the Acri.Twin asymmetric diffractive bifocal intraocular lens system

Abstract: Asymmetric bilateral implantation of the Acri. Twin IOL gave good simultaneous distance and near vision with improved contrast sensitivity under photopic and mesopic conditions. Differences between monocular and binocular visual acuity and contrast sensitivity were obtained because of the distance-/near-weighted light distribution of Acri. Twin IOLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Two separate focal points along the optical axis are generated to provide good unaided distance and near vision as well as functional intermediate vision. Current designs of pseudoaccommodative IOLs use diffractive optics [1][2][3][4][5] , zones of differing refractive power [6][7][8][9] or both principles (hybrid IOLs) [10][11][12][13] . Recent studies performed on hybrid AcrySof ReSTOR IOL pointed out satisfactory visual results.…”
Section: Introductionmentioning
confidence: 99%
“…Two separate focal points along the optical axis are generated to provide good unaided distance and near vision as well as functional intermediate vision. Current designs of pseudoaccommodative IOLs use diffractive optics [1][2][3][4][5] , zones of differing refractive power [6][7][8][9] or both principles (hybrid IOLs) [10][11][12][13] . Recent studies performed on hybrid AcrySof ReSTOR IOL pointed out satisfactory visual results.…”
Section: Introductionmentioning
confidence: 99%
“…Jacobi et al [5] developed this new concept, asymmetrical bilateral multifocal IOL implantation to enhance visual performance of the multifocal IOL after binocular implantation. Alfonso et al [7] assessed the quality of vision in 343 patients who had implantation of asymmetric Acri.Twin bifocal diffractive IOLs, and reported that BCVA and BCNVA were 0.031±0.059 and 0.005±0.024 respectively. Similarly, Schmidinger et al…”
Section: Discussionmentioning
confidence: 99%
“…Safety and efficacy indexes obtained in the present study were slightly better than obtained after RLE and AcrySof ReSTOR implantation. And also, although this is not a comparative study of symmetric and asymmetric implantation, through symmetric implantation we can avoid the problems associated with the choice of the dominant eye [34,35] and this may solve binocular vision intolerance reported by some patients to different light distribution between eyes [7], which achieved equally good visual outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations